Are working hours a new driver of inequality? On the relation between hours inequality, earnings inequality, and collective bargaining in Germany - Stefanie Gerold; Ulrike Stein (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2020)
This paper studies the relationship between inequalities in working hours and overall earnings inequality in Germany between 2006 and 2014, and the role of declining collective bargaining coverage. Using data from the German Structure of Earnings Survey (GSES), a variance decomposition of earnings inequality reveals that hours inequality and the covariance between wages and hours become more important over time in determining earnings inequality. Based on unconditional quantile regressions, we show that the presence of collective agreements tends to increase working hours at the bottom of the distribution, and lowers them at the top end of the distribution, while controlling for individual and firm-specific characteristics. These findings imply that union presence is not only able to compress wage inequality, but might reduce earnings inequality through a compression of working hours.
urn:nbn:de:101:1-2020052612233684779628
Keywords: J22; J31; J52; C31; D31; 330; inequality; working hours; collective bargaining; decomposition; unconditional quantile regression; RIF regressions; Structure of Earnings Survey